The dilemma of newspaper cartoonists: perspectives from Nigerian practitioners - Semiu Musa Bello (The Indonesian Journal of Communication Studies, 2021)
Cartooning in journalism practice is, by nature and as demonstrated in many parts of the world, an intelligent journalistic endeavour undertaken by cartoonists or cartoon journalists to put those in power to accountability and responsibility. It is a special genre of journalism profession to disseminate information graphically and illustratively to members of the public. Cartoonists strategically use cartoons and their journalistic drawings to portray social evils, corrupt practices, criticise policies and programmes of government, actions of various corporate bodies, religious organisations and individuals’ misdemeanours in a satirical and comic form. In the course of performing these multifarious functions in society, cartoonists have been subjected to an array of challenges or have been made to go through various challenges and consequently thrown into dilemma. Investigating these challenges and how cartoon journalists have been able to cope in their trade and profession define the thesis of this study. Operationally, the study employs the indepth interview research method to garner the perspectives of cartoon practitioners in Nigeria to determine the dimension of the challenges they encounter in their profession and what factors keep them in the profession. Among other challenges, this study find that cartoon journalists encounter proprietor’s influence, poor remuneration, lower estimation and respect by editors and other superior officers in media organisations as well as threats, insecurity and attacks from the politicians. Cartoon journalists, however, remain motivated and committed to their profession due to personal interest/passion and love for public interest.